Effectiveness of Reproductive Health Education Through Leaflets and Personal Hygiene Practices on Menstrual Knowledge and Behavior of Vocational School Students In West Java - Retno Retno; Arifah Rakhmawati; Achmad Fauzi (Universitas Pahlawan Tuanku Tambusai, 2026)
Hemodialysis is a kidney replacement therapy that must be performed regularly and long-term. Fatigue is a major clinical problem frequently experienced by patients with chronic kidney disease (CKD) undergoing hemodialysis. This condition is chronic and multifactorial, characterized by decreased physical energy, impaired concentration, low motivation, and limitations in performing daily activities. Fatigue not only reduces patients' quality of life but also contributes to poor therapy adherence, psychosocial disorders, and an increased risk of long-term complications. This study used a quantitative approach with a one-group pretest-posttest design, involving one group of hemodialysis patients who received acupressure therapy intervention. Respondents' fatigue levels were measured before and after acupressure administration to assess the intervention's effectiveness in reducing fatigue. To determine the effectiveness of acupressure in reducing fatigue levels in patients with chronic kidney disease undergoing hemodialysis at Anna Medika Hospital, North Bekasi in 2025.The analysis of the effectiveness of acupressure in reducing fatigue in hemodialysis patients at Anna Medika Hospital in 2025. The data showed a p-value of 0.028 (p-value <0.05), indicating a significant effect of acupressure on reducing fatigue in hemodialysis patients at Anna Medika Hospital in 2025 before and after the intervention.Acupressure therapy has been proven effective in reducing fatigue in hemodialysis patients at Anna Medika Hospital in 2025. The results of this study are expected to inform the development of a socialization program, specifically